Vascular type Ehlers-Danlos Syndrome with fatal spontaneous rupture of a right common iliac artery dissection: case report and review of literature - Abayazeed, Aly (EduRad, 2014)
Vascular Ehlers-Danlos Syndrome (previously Ehlers-Danlos IV) is a rare autosomal dominant collagen vascular disorder caused by a 2q31 COL3A1 gene mutation encoding pro-alpha1 chain of type III collagen (in contrast to classic Ehlers-Danlos, caused by a COL5A1 mutation). The vascular type accounts for less than 4% of all Ehlers-Danlos cases and usually has a poor prognosis due to life threatening vascular ruptures and difficult, frequently unsuccessful surgical and vascular interventions. In 70% of cases, vascular rupture or dissection, gastrointestinal perforation, or organ rupture is a presenting sign. We present a case of genetically proven vascular Ehlers-Danlos with fatal recurrent retroperitoneal hemorrhages secondary to a ruptured right common iliac artery dissection in a 30-year-old male. This case highlights the need to suspect collagen vascular disorders when a young adult presents with unexplained retroperitoneal hemorrhage, even without family history of such diseases.